Simulation of radioecological processes in mountain ecosystems specific to Ukraine - Петрусенко, В.П.; Кутлахмедов, Ю.О. (Proceedings of National Aviation University, 2007)
To analyze and simulate radioecological processes in mountain ecosystems typical for regions of Ukraine the method of the box (chamber) models is used. The real values of the rate of radionuclide exchange between the elements of a mountain landscape are specified on the basis of the literature data and the data of experts. Our results on simulation of slope ecosystems were adopted for mountain landscape with considerable greater rate of redistribution of radionuclides (Cs–137). Estimation of ecological safety for a mountain landscape contaminated with radionuclides is carried out on the basis of estimation of the radioactive doses affected people making use of a typical mountain ecosystem for production activity and recreation.It is shown that in a mountain ecosystem there is a rapid accumulation of the limit human radiation dose which may account for 6 – 17% of the initial amount in the ecosystem. It is shown that the events where not only the mountain top but all the elements of the mountain landscape are exposed to initial contamination are the most dangerous.